Establishing genetic and environmental parameters for ostrich (Struthio camelus domesticus) growth and slaughter characteristics - Engelbrecht, Anel (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.